2011
DOI: 10.1097/brs.0b013e3181dfce9e
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Tumor Necrosis Factor-α and CD68 in High-Intensity Zone of Lumbar Intervertebral Disc on Magnetic Resonance Image in the Patients With Low Back Pain

Abstract: The results of this study indicate that HIZ may be a specific signal for the inflammatory reaction of painful intervertebral disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 23 publications
5
40
1
Order By: Relevance
“…Histological findings showed that the displaced mass with the HIZ contained many fibroblast-like cells and the matrix was fibrotic. This is in good agreement with previous histological studies on the HIZ [8, 9]. …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Histological findings showed that the displaced mass with the HIZ contained many fibroblast-like cells and the matrix was fibrotic. This is in good agreement with previous histological studies on the HIZ [8, 9]. …”
Section: Discussionsupporting
confidence: 93%
“…Similar clinical studies followed [57]. Chen et al [6] reported a correlation between the HIZ and positive concordant pain on discography, and Peng et al [8] and Dongfeng et al [9] found inflammation and neovascularization on histological analysis of disc material in the HIZ. Physicians should therefore be aware of the significance of the HIZ when diagnosing discogenic pain.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations